Researcher or epidemiologist? For the creation and development of the specialty of Epidemiology in Health Sciences - Oyola-García, Alfredo Enrique (2017)
Mr. Editor The National Council of Science and Technology (CONCYTEC) has been developing a recognized work to increase the scientific production of quality in our country. Among other actions, it has created the National Directory of Researchers (DINA) and the National Registry of Researchers in Science and Technology (REGINA). Indirectly, these actions have caused some health professionals (1) to postulate the following: a) CONCYTEC defines who is and who is not a 'researcher', and b) A 'researcher' who does not publish in indexed journals is a theoretician and does not It must be named as such. Next we will discuss these two assertions.